Identification of AREB/ABF Gene Family Involved in the Response of ABA under Salt and Drought Stresses in Jute (Corchorus olitorius L.) - Manuel Sebastian Fiallos-Salguero; Jing Li; Yunqing Li; Jiantang Xu; Pingping Fang; Yankun Wang; Liwu Zhang; Aifen Tao (Plants, 2023)
The abscisic acid (ABA)-responsive element binding protein/ABRE-binding factor (AREB/ABF) subfamily members are essential to ABA signaling pathways and plant adaptation to various environmental stresses. Nevertheless, there are no reports on AREB/ABF in jute (Corchorus L.). Here, eight AREB/ABF genes were identified in the C. olitorius genome and classified into four groups (A–D) based on their phylogenetic relationships. A cis-elements analysis showed that CoABFs were widely involved in hormone response elements, followed by light and stress responses. Furthermore, the ABRE response element was involved in four CoABFs, playing an essential role in the ABA reaction. A genetic evolutionary analysis indicated that clear purification selection affects jute CoABFs and demonstrated that the divergence time was more ancient in cotton than in cacao. A quantitative real-time PCR revealed that the expression levels of CoABFs were upregulated and downregulated under ABA treatment, indicating that CoABF3 and CoABF7 are positively correlated with ABA concentration. Moreover, CoABF3 and CoABF7 were significantly upregulated in response to salt and drought stress, especially with the application of exogenous ABA, which showed higher intensities. These findings provide a complete analysis of the jute AREB/ABF gene family, which could be valuable for creating novel jute germplasms with a high resistance to abiotic stresses.